Filsafat Ilmu Sebagai Sarana Berfikir Ilmiah dalam Ilmu Pengetahuan: Integrasi Perspektif Islam dan Maqāṣid Syarī‘Ah - Mutaqin, Deden Zaenal; Syukri, Ahmad; Yenti, Zarfina (Universitas Batanghari Jambi, 2026)
The philosophy of science plays a fundamental role in shaping rational, systematic, and responsible scientific thinking. In the development of modern science, scientific thinking is often limited to a methodological-positivistic dimension and separated from the value dimension. This article aims to broaden the horizon of scientific thinking by integrating the philosophy of science with an Islamic perspective and the maqāṣid al-syarī‘ah (objectives of Islamic law). This research uses a library research method with a philosophical-normative approach and conceptual analysis. The results show that the philosophy of science functions as a meta-theoretical tool that guides the ontology, epistemology, and axiology of science. In Islam, scientific rationality is rooted in monotheism and driven by revelation, while the maqāṣid al-syarī‘ah serves as an axiological compass that ensures that science is oriented towards the benefit of God. This integration creates a scientific thinking paradigm that is holistic, ethical, and relevant to the challenges of contemporary science.